Surface Characterization and Assessment of Biofilm Formation on Two Titanium-Based Implant Coating Materials - Shokeen, Bhumika; Zamani, Leila; Zadmehr, Sara; Pouraghaie, Sevda; Ozawa, Ryotaro; Yilmaz, Burak; Lilak, Sam; Sharma, Shivani; Ogawa, Takahiro; Moshaverinia, Alireza; Lux, Renate (Frontiers in Dental Medicine, 2021)
Implant-related oral diseases such as peri-implantitis and peri-mucositis are largely initiated by bacterial colonization on artificial implant surfaces. Therefore, implant and abutment material characteristics that minimize bacterial attachment and subsequent biofilm formation are important factors in reducing the risk of infection-related implant failure. This study compares the properties of two different titanium-based implant coating materials, titanium nitride (TiN) and titanium carbon nitride (TiCN). Surface hydrophilicity/ hydrophobicity and roughness were evaluated via contact angle measurements and surface profiling with white light interferometry, respectively. TiN-coated surfaces were hydrophobic according to its contact angle higher than 72.7º, whereas TiCN-coated surfaces were hydrophilic with its contact angle of 53.6º. The average roughness (Ra) was greater for TiCN than TiN with the root mean square roughness (Rq) being significantly higher. These findings are in contrast to the common understanding for titanium-based materials that surface roughness and hydrophobicity are positively correlated. A well-established saliva-based oral microbial biofilm model was employed to compare bacterial attachment and biofilm formation on TiN and TiCN. Growth conditions included relevant host components such as blood as well as the presence or absence of dietary carbohydrates. The accumulated biomass was measured by crystal violet staining and the bacterial community profiles of the attached biofilms were determined via 16S rRNA gene microbiome sequencing at different time points over a seven-day period. At all time points, TiCN showed significantly less bacterial attachment and biofilm formation compared to TiN. This implied the importance of the hydrophilic state over surface roughness as parameter for the prevention of oral microbial attachment. Although, the biofilm community composition was very similar on both materials, environmental growth conditions resulted in significantly different bacterial profiles independent of the surface. In conclusion, TiCN coating produced a unique titanium surface which is rougher but more hydrophilic. TiCN-coated surfaces exhibited reduced bacterial attachment and biofilm formation in comparison to TiN coating. This coating technique can be further explored to improve implant and abutment success.